Evaluation of in-office tooth whitening treatment with violet LED: protocol for a randomised controlled clinical trial - Lara Jansiski Motta; Anna Carolina Ratto Tempestini Horliana; Sandra Kalil Bussadori; Maria Fernanda Setúbal Destro Rodrigues; Ana Eliza Castanho Garrini dos Santos; Marcelo Mendes Pinto; Dácio Antonio Pantano Junior; Aldo Brugnera Jr; Fátima Antonia Aparecida Zanin (BMJ Open)
Introduction In-office tooth whitening treatment using violet light emited diode (LED) (405 nm) is a novel bleaching method that causes less sensitivity while offering the same effectiveness as the gold standard (35% hydrogen peroxide, H2O2). This study describes a protocol for the first randomised controlled clinical trial to compare the effects of the two methods.Methods and analysis Eighty patients will be divided into four groups: G1 violet LED; G2 violet LED +35% carbamide peroxide; G3 35% H2O2 and G4 violet LED +gingivoplasty. Colour will be measured at baseline, immediately after the first session and at the 15 and 180 days follow-up using the Vita Classical and the digital Easyshade V spectrophotometer (Vita, Zahnfabrik, Germany). Sensitivity after whitening will be measured using the Visual Analogue Scale at baseline and at each session in all groups and in all follow-ups. The tissue removed during gingivoplasty (G4) will be submitted to immunohistochemical analysis for the determination of inflammatory changes caused by violet LED. The Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) will be evaluated before, as well as at established time point controls. The results will be expressed as mean and SD values. After determining the normality of the data, a one-way repeated-measures analysis of variance will be used for the comparison of data with normal distribution and the Kruskal-Wallis test will be used for data with non-normal distribution. A p<0.05 will be considered indicative of statistical significance. After determining the normality of the data, the Kruskal-Wallis test will be used for non-parametric data. Multivariate analysis of variance (MANOVA) and the Wilcoxon test will be used for comparing data from the PIDAQ.Ethics and dissemination This protocol has been approved by the Human Research Ethics Committee of UniversidadeNove de Julho (certificate: 2.034.518). The findings will be published in a peer-reviewed journal.Trial registration number NCT03192852; Pre-results.